DETERMINANTS OF CAREER READINESS OF HOSPITALITY AND TOURISM MANAGEMENT STUDENTS COVID-19 PANDEMIC - Suci Purwandari; Singgih Purnomo; Jasur Ehsonov (Bajang Institute, 2024)
The COVID-19 pandemic has negatively affected the hospitality and tourism industry, decresing the self-efficacy of hospitality and tourism management students towards their future and careers. This study aims to investigate how industrial work practices, family environment, curriculum, campus support, and self-efficacy affect the career readiness of hospitality and tourism management students. This study found that self-efficacy, perceived curriculum, and campus support significantly affect students' career readiness. Industrial work practices and family environment influence self-efficacy. This study also found that self-efficacy affects the relationship between industrial work practices and family environment on students' career readiness. The results of this study provide insight to managers and education at hospitality universities to improve the competitiveness of hospitality and tourism programs, especially in developing curricula, providing expertise support, and student self-efficacy.